Copper Dressings to the Wound Rescue after Everything Else Failed: Case Report - Weitman, Cernica Chausha; Roth, Tohar; Borkow, Gadi (Archives of Clinical and Medical Case Reports, 2022)
We report a dramatic case in which an initially minor superficial wound with an area of approximately 4 cm2 in diameter, increased in size to ~300 cm2 and more than 1cm deep, during 8 months of hospitalization. This deterioration occurred despite a wide range of standard of care procedures, such as OR debridement of necrotic tissue, systemic and local antibiotics administration, application of a variety of antimicrobial wound dressings, wound washes, Negative Pressure Wound Therapy, pressure chamber treatment, and two skin grafts after escharotomy. Resolution of the wound progression, subsequent granulation tissue formation, epithelialization, wound healing and almost complete wound closure- was achieved only after treatment with copper oxide impregnated wound dressings. This case strongly supports the potential role of copper in the healing process of hard-to-heal wounds.